The Implementation of Translanguaging Approach in Rural School: A Case Study - Edy, Nur Azizah Dikastuti; Ashadi, Ashadi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores the implementation of the translanguaging approach by English teachers in rural junior high schools in the Special Region of Yogyakarta, Indonesia. Employing a qualitative multiple case study design, the research involved three English teachers selected through maximum variation sampling. Data were collected through non-participant classroom observations, semi-structured interviews, and document analysis. Guided by Rabbidge’s (2019) five-set translanguaging strategy framework, the findings reveal that teachers utilized various strategies to facilitate student comprehension and engagement. The results demonstrate that translanguaging practices enabled teachers to create more inclusive learning environments by bridging linguistic gaps and supporting multilingual learners. This study contributes to the growing body of research on translanguaging in English as a Foreign Language (EFL) settings.